Microsatellite analysis for differentiating the origin of renal angiomyolipoma and involved regional lymph node. Issue 1 (December 2017) - Tan, Ping; Xu, Huan; Jiang, Yong; Yang, Lu; Zou, Yan; Liu, Liangren; Liu, Nian; Cao, Dehong; Fan, Yu; Li, Qiyuan; Wei, Qiang
Abstract Renal angiomyolipoma (AML) with the regional lymph node (LN) involved leads to a question of metastasis versus multicentric origin when their histology are similar. As the genomic instability is a common feature of cancer, we hypothesized that independently arising neoplasms in an individual patient would exhibit measurable genomic variation, facilitating the discrimination of tumor lineage and relatedness. Our study enrolled 12 patients who were diagnosed with nodal-involved renal AML at West China Hospital. Genomic DNA from kidney and lymph node lesion from individuals was analyzed through PCR-based analysis which using six microsatellite markers to identify discordant allelic variation. The results showed all 12 patients underwent surgical treatment and none suffered local recurrence or distant metastasis during the follow-up. Ten patients of the included cases showed a consistent trend that all corresponding to six microsatellite markers were detected in DNA from renal AMLs but were reduced or not observed in DNA from the paired LN. With this technique, a possible lineage relationship cannot be excluded between renal AMLs and LN. Thus when enlarged LN were found in images, active surveillance should be taken into consider; if enlarged LN were found intraoperatively, LN resection might be necessary to demonstrate their pathological nature.